American world literature an introduction - Giles, Paul (Hoboken, NJ Wiley-Blackwell, 2018)
"This book is designed to offer an overview of ways in which the subject areas of American Literature and World Literature have converged (and diverged) over the past twenty or thirty years. American literature is now widely regarded as engaging with global rather than merely with local or national phenomena, and American World Literature: An Introduction attempts to set these changing conceptions of the subject in both critical and historical context. It also suggests how this perception of American literature as a global or "world" phenomenon has varied significantly across time, so that the intellectual investments of Cotton Mather in ideas of universal forms during the seventeenth century can be productively compared and contrasted to the resurgence of nationalist and transnational templates in the poetry of Walt Whitman two hundred years later. In his preface to Literary Theory: An Introduction, published in 1983, Terry Eagleton wrote of how he had "tried to popularize rather than vulgarize the subject," and my intention here similarly is to address these complex historical and methodological issues in a way that might enlighten readers with little experience in the academic study of American literature, while still providing a sufficiently rounded view of these multifaceted matters to provoke interest in readers for whom the broad outlines of these debates will be more familiar"-- Provided by publisher.
The Theory of American World Literature -- Early American Literature in the World -- National/Global: The Framing of Nineteenth-Century American Literature -- The Worlds of American Modernism -- Postmodernism, Globalization and U.S. Literary Culture.
Includes bibliographical references and index.
Keywords: American literature -- History and criticism; Comparative literature